An Overview of the Effectiveness of Bicycle Helmet Designs in Impact Testing - Abderezaei, Javid; Rezayaraghi, Fargol; Kain, Brigit; Menichetti, Andrea; Kurt, Mehmet (Frontiers in Bioengineering and Biotechnology, 2021)
Cycling accidents are the leading cause of sports-related head injuries in the U.S. Conventional bicycle helmets typically consist of polycarbonate shell over Expanded Polystyrene (EPS) foam and are tested with drop tests to evaluate a helmet's ability to reduce head kinematics. Within the last decade, novel helmet technologies have been proposed to mitigate brain injuries during bicycle accidents, which necessitates the evaluation of their effectiveness in impact testing as compared to the conventional helmets. In this paper, we reviewed the literature to collect and analyze the kinematic data of drop test experiments carried out on helmets with different technologies. In order to provide a fair comparison across different types of tests, we clustered the datasets with respect to their normal impact velocities, impact angular momentum, and the type of neck apparatus. When we analyzed the data based on the impact velocity and angular momentum, we found that the bicycle helmets that used rotation damping based technology, namely MIPS, had significantly lower peak rotational acceleration (PRA) and Generalized Acceleration Model for Brain Injury Threshold (GAMBIT) at low-velocity impact tests and low angular momentum as compared to the conventional EPS/EPP liner helmets, respectively (p<0.01). While in the impact velocity clustered group, SPIN helmets did not show significant decrease of PRA as compared to the conventional helmets, in the impact angular momentum clustered group this helmet showed significant improvement (p<0.05). Other recently developed helmets that utilize collapsible structures in their liner, such as WaveCel and Koroyd, had conflicting results in terms of significant reduction in head accelerations. In both of the impact velocity and angular momentum group, helmets based on the WaveCel technology had significantly lower peak linear acceleration (PLA), PRA, and GAMBIT at low impact velocities as compared to the conventional helmets, respectively (p<0.05). The protective gear with the airbag technology, namely Hovding, also performed significantly better compared to the conventional helmets in the analyzed kinematic-based injury metrics (p<0.001), possibly due to its advantage in helmet size and stiffness. Our findings highlight the importance of incorporating the new technologies in the conventional helmet designs for better prevention of traumatic brain injury (TBI).